ANALYSIS OF FINANCIAL ACHIVEMENT BEFORE AND DURING THE CORONA VIRUS PANDEMIC IN THE AUTOMOTIVE SUB – SECTOR - Hastuti, Rini Tri; Lestari, Adelia (International Journal of Application on Economics and Business, 2025)
The Corona Virus pandemic has had a systemic impact on all sectors, especially the business sector. This impact has resulted in the collapse of business pillars in several sectors, but has also resulted in extraordinary growth in several other sectors. Corona Virus has changed the lifestyle of society as a whole. Starting from people who have to keep their distance from each other to the decline in sales due to the decline in consumption and people's purchasing power. This has further impacted business closures and massive layoffs. This pandemic has disrupted the global economy and has had an impact on automotive sub-sector companies. The impact of this pandemic is very relevant, and the automotive sub-sector around the world is forced to face major challenges in maintaining its financial achivement. Every corporate certainly has a goal to generate maximum profit. If the corporate can achieve this goal, then the corporate will be considered to have good corporate achivement and quality. To assess the quality of a corporate, it can be seen from its financial achivement. Therefore, this study aims to identify whether or not there is a dissimilar in financial achivement before and during the Corona Virus pandemic, with 2018-2019 as the pre-pandemic period and 2020-2021 as the pandemic period by taking the automotive sub-sector listed on the Indonesia Stock Exchange as the object of studied. Financial achivement in this test will use the profitability comparation calculated using return on assets, the solvency comparation calculated using the debt on asset comparation, and the activity comparation calculated using total asset turnover. Data is processed and analyzed using SPSS 26 after going through purposive sampling. The test results prove that there is a relevant dissimilar in ROA before and during the Corona Virus pandemic. Meanwhile, the test results prove that there is no relevant dissimilar for DER and TATO before and during the Corona Virus pandemic. The implication of this study is to provide implications that automotive sub-sector business actors must improve their corporate's achivement with the resources they have effectively and minimize all risks during the Corona Virus pandemic, so that the corporate's profitability improves and recovers quickly from the impact of Corona Virus